Reactive tabu search approach for solving capacitated arc routing problem [electronic resource] - Norhazwani Md. Yunos, 1985-; Fakulti Sains (2009)
Thesis (Sarjana Sains (Matematik)) - Universiti Teknologi Malaysia, 2009